2014
DOI: 10.1039/c4ta02192d
|View full text |Cite
|
Sign up to set email alerts
|

Slightly hydrogenated TiO2 with enhanced photocatalytic performance

Abstract: Slightly hydrogenated white TiO2 nanoparticles show enhanced photocatalytic performance due to their increased surface defects, while gray or black H-TiO2 nanoparticles display much worse catalytic performances due to the formation of bulk defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
137
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 192 publications
(157 citation statements)
references
References 54 publications
13
137
1
4
Order By: Relevance
“…It is likely that surface oxygen vacancies are responsible for the enhanced photocatalytic activity [39,70,75], while bulk oxygen vacancies act as trap states and charge carrier recombination centers [76]. Studies also showed that surface Ti 3+ defects could enhance hole trapping and thus facilitate the separation of photo-excited electrons and holes [57], while bulk Ti 3+ sites acted as charge annihilation centers, leading to enhanced nonradiative recombination and shorter lifetime of electrons and holes [57,60]. In addition, Ti 3+ ions with oxygen vacancies can improve the electrical conductivity of TiO 2 [73,77], which may enhance the charge transport and charge-transfer reaction [73].…”
Section: Defectsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is likely that surface oxygen vacancies are responsible for the enhanced photocatalytic activity [39,70,75], while bulk oxygen vacancies act as trap states and charge carrier recombination centers [76]. Studies also showed that surface Ti 3+ defects could enhance hole trapping and thus facilitate the separation of photo-excited electrons and holes [57], while bulk Ti 3+ sites acted as charge annihilation centers, leading to enhanced nonradiative recombination and shorter lifetime of electrons and holes [57,60]. In addition, Ti 3+ ions with oxygen vacancies can improve the electrical conductivity of TiO 2 [73,77], which may enhance the charge transport and charge-transfer reaction [73].…”
Section: Defectsmentioning
confidence: 99%
“…More importantly, oxygen vacancies and/or Ti 3+ defects extend the photoresponse of TiO 2 from UV to visible light region, which leads to high visible-light photocatalytic activity [14,59,[67][68][69][70][71][72]. Note that high density of crystal defects, especially bulk defects, may accelerate electron-hole recombination as defects can International Journal of Photoenergy act as charge annihilation centers [57,73,74]. It is likely that surface oxygen vacancies are responsible for the enhanced photocatalytic activity [39,70,75], while bulk oxygen vacancies act as trap states and charge carrier recombination centers [76].…”
Section: Defectsmentioning
confidence: 99%
See 3 more Smart Citations